2014
DOI: 10.5861/ijrse.2014.888
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ perspectives on child care quality and satisfaction in Taiwan

Abstract: Parents are important stakeholders when demanding quality child care services, and it is necessary to take parents' perspectives on child care quality seriously. The purpose of this study was to investigate Taiwanese parents' perceptions regarding the importance of quality, and satisfaction with preschools based on participants' demographic characteristics, child's ages, and types of schools. Convenience sampling was utilized in this study. Data were collected from 810 participants with at least one three-to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
2
4
0
Order By: Relevance
“…The study findings suggest that high-income levels motivate working mothers to send their children to childcare centres of their choice, which are expected to provide quality service; hence, most of them tend to be satisfied with the service quality of childcare centres. The results concur with the findings of Jang et al (2014) and Torquati et al (2011). The findings are also in line with those of Suppramaniam et al (2019), who point out that the relationship between school popularity and parents' income levels had a significant impact on private school selection.…”
Section: Working Mothers' Perception Of Childcare Service Quality By ...supporting
confidence: 92%
See 2 more Smart Citations
“…The study findings suggest that high-income levels motivate working mothers to send their children to childcare centres of their choice, which are expected to provide quality service; hence, most of them tend to be satisfied with the service quality of childcare centres. The results concur with the findings of Jang et al (2014) and Torquati et al (2011). The findings are also in line with those of Suppramaniam et al (2019), who point out that the relationship between school popularity and parents' income levels had a significant impact on private school selection.…”
Section: Working Mothers' Perception Of Childcare Service Quality By ...supporting
confidence: 92%
“…The study finding is conformist to the literature of Jang et al (2014), Mgata (2017) and Torquati et al (2011), which reported the direct relationship between child's age and childcare service quality perception in the education sector. Jang et al (2014) findings revealed that parents of three-and four-year-old children reported more satisfaction with childcare services. Keiningham et al (2006) findings show that parents' satisfaction was most important in retaining children, especially when they were very young (up to one year).…”
Section: Working Mothers' Perception Of Childcare Service Quality By ...supporting
confidence: 91%
See 1 more Smart Citation
“…Research consistently emphasises the importance of the quality of centre-based childcare and its direct impact on parent views and satisfaction (4,14). Positive interactions between teachers and children are crucial for parental satisfaction.…”
Section: Perspectives Of Parents On Quality Childcarementioning
confidence: 99%
“…Poor results are consistent with similar studies abroad. Mothers education and marital status are demographic characteristics the importance of which in the parents´ preschool choice has been proved in countries as diverse as Taiwan (Jang, Moore, & Lin, 2014), Italy (Scopelliti & Musati, 2013) or the United states (Fantuzzo, Perry, & Childs, 2006).…”
Section: Parents Satisfaction With the Child´s Developmental Progressmentioning
confidence: 99%